Flexible Polypyrrole@Fe2O3@Stainless Steel Yarn Composite Electrode for Symmetric Thread‐Like Supercapacitor with Extended Operating Voltage Window in Li2SO4‐Based Aqueous Electrolyte. (24th September 2020) - Zuo, Wusheng; Zang, Limin; Wang, Xue; Liu, Qifan; Qiu, Jianhui; Liang, Chunliu; Liu, Xin; Yang, Chao
Abstract: A flexible symmetric thread‐like supercapacitor (TSC) with high operating voltage window and good electrochemical performance is manufactured, that fulfills the requirements of wearable electronics. First, iron oxide (Fe2 O3 ) nanosheets are directly grown in situ on the surface of stainless steel yarn (SSY) by an acid corrosion and self‐oxidation process, and then a polypyrrole (PPy) coating is covered on the surface of Fe2 O3 nanosheets via chemical oxide method to obtain the thread‐like PPy@Fe2 O3 @SSY composite electrode. The electrode achieves a wide potential range of −1.0–0.8 V (versus Ag/AgCl) and a high areal specific capacitance of 667.8 mF cm −2 with outstanding galvanostatic charge/discharge cycling stability of 87.5% capacitance retention after 10 000 cycles in 1 m lithium sulfate (Li2 SO4 ) aqueous solution. The symmetric TSC based on the PPy@Fe2 O3 @SSY electrode and carboxymethyl cellulose sodium salt/Li2 SO4 gel electrolyte exhibits a wide operating voltage window of 1.8 V, and its maximum energy density can reach 39.3 μWh cm −2 . Additionally, the TSC demonstrates excellent electrochemical performance under various bending states and a bending cycling test. The preparation method and raw materials are low‐cost and scalable, and the overall performance of the TSC is excellent, which makes this device a promising energy storage device for wearable electronics. Abstract : Stainless steel yarn (SSY) is used as a support, iron source and current collect at the same time to obtain a binder‐free PPy@Fe2 O3 @SSY electrode without the use of other ferrous chemicals. Then a symmetric thread‐like supercapacitor (TSC) based on the PPy@Fe2 O3 @SSY electrode with high operating voltage window of 1.8 V in neutral aqueous electrolyte and excellent electrochemical performance is fabricated.